2023
DOI: 10.32942/x2z883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing giant sequoia mortality and regeneration following high severity wildfire

Abstract: Fire is a critical driver of giant sequoia (Sequoiadendron giganteum [Lindl.] Buchholz) regeneration. However, fire suppression combined with the effects of increased temperature and severe drought have resulted in fires of an intensity and size outside of the historical norm. As a result, recent mega-fires have killed a significant portion of the world’s sequoia population (13 to 19%), and uncertainty surrounds whether severely affected groves will be able to recover naturally, potentially leading to a loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
0
4
2
Order By: Relevance
“…In our Nelder Grove data, median sequoia seedling density for areas with RdNBR values <477 was 255/ha, while areas with RdNBR values 477-899 had a median sequoia seedling density of 2165/ha, and areas with RdNBR ≥900 had a median density of 2674/ha (nearly 17 times higher than the median sequoia seedling density at 5 years after prescribed fires in Stephenson et al, 2023). As Soderberg et al (2024) reported results 1 year postfire, our results reported 6 years postfire, may not be inconsistent with theirs. Sequoia seedling density may be relatively lower in areas with RdNBR values ≥900 at 1 or 2 years postfire, and such areas may provide good conditions for sequoia seedling survival, growth, and perhaps additional germination and establishment, which could shift the relative seedling density higher in such very high-severity areas by several years postfire.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…In our Nelder Grove data, median sequoia seedling density for areas with RdNBR values <477 was 255/ha, while areas with RdNBR values 477-899 had a median sequoia seedling density of 2165/ha, and areas with RdNBR ≥900 had a median density of 2674/ha (nearly 17 times higher than the median sequoia seedling density at 5 years after prescribed fires in Stephenson et al, 2023). As Soderberg et al (2024) reported results 1 year postfire, our results reported 6 years postfire, may not be inconsistent with theirs. Sequoia seedling density may be relatively lower in areas with RdNBR values ≥900 at 1 or 2 years postfire, and such areas may provide good conditions for sequoia seedling survival, growth, and perhaps additional germination and establishment, which could shift the relative seedling density higher in such very high-severity areas by several years postfire.…”
Section: Discussioncontrasting
confidence: 75%
“…Thus, important management decisions, with potentially long-term effects, are being made in the absence of scientific evidentiary support and essential knowledge. Soderberg et al (2024) reported lower postfire giant sequoia seedling density at the upper end of the high-severity fire spectrum (particularly ≥900 RdNBR) at 1 year postfire. Our results, at 6 years postfire, do not suggest a decrease.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations